2022
DOI: 10.1038/s41523-021-00374-x
|View full text |Cite
|
Sign up to set email alerts
|

HBXIP induces anoikis resistance by forming a reciprocal feedback loop with Nrf2 to maintain redox homeostasis and stabilize Prdx1 in breast cancer

Abstract: Anoikis resistance is an essential prerequisite for tumor metastasis, but the underlying molecular mechanisms remain unknown. Herein, we report that the oncoprotein hepatitis B X-interacting protein (HBXIP) is prominently upregulated in breast cancer cells following ECM detachment. Altering HBXIP expression can impair the anchorage-independent growth ability of tumor cells. Mechanistically, HBXIP, which binds to Kelch-like ECH-associated protein 1 (Keap1) to activate nuclear factor E2-related factor 2 (Nrf2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Anoikis is a form of programmed cell death, which is essential for the survival of tumor cells after detachment from the extracellular matrix (ECM) (Xiao et al, 2019;Zhou et al, 2022). The generation of anoikis resistance in aggressive tumor cells has been identified as a key factor in tumor progression (Berezovskaya et al, 2005;Kim et al, 2012;Yu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Anoikis is a form of programmed cell death, which is essential for the survival of tumor cells after detachment from the extracellular matrix (ECM) (Xiao et al, 2019;Zhou et al, 2022). The generation of anoikis resistance in aggressive tumor cells has been identified as a key factor in tumor progression (Berezovskaya et al, 2005;Kim et al, 2012;Yu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Anoikis is a special apoptotic that is a consequence of the loss of or improper cell adhesion, which is paramount for the survival of tumor cells following separation from the extracellular matrix (ECM) [ 14 , 15 , 16 ]. Previous studies have found that an anti-anoikis mechanism in cancer cells is pivotal to cancer progression [ 17 , 18 ]. In recent years, although a multitude of mechanisms of anoikis in tumors have been proposed and validated, the role of prognostic molecules of anoikis-related genes underlying tumors remains to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggested anoikis occurred through intrinsic/extrinsic pathways and could be triggered by several intracellular signals such as DNA damage and endoplasmic reticulum stress (Li et al, 2019;Zhi et al, 2022). Anoikis is essential for cancer cell survival through the detachment from ECM, and anoikis resistance is a key factor in cancer invasion and metastasis (Berezovskaya et al, 2005;Kim et al, 2012;Kakavandi et al, 2018;Xiao et al, 2019;Yu et al, 2022;Zhou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%